A postal survey to identify and describe nurse led clinics in genitourinary medicine services across England. Issue 2 (1st April 2002) - Miles, K; Penny, N; Mercey, D; Power, R
Abstract : Background: Nurses in genitourinary medicine (GUM) services are progressively extending their roles to conduct "comprehensive care" nurse led clinics. In such roles the nurse coordinates the first line, comprehensive care of patients presenting with sexual health conditions and issues. Objectives: To identify and describe comprehensive care nurse led clinics in GUM services across England. Methods: A postal questionnaire consisting of 17 closed response questions was sent to 209 GUM services across England. A second questionnaire was sent to non-responders to increase the response rate. Data were single entered and analysed using spss . Results: Of the 190 GUM clinic respondents (91% response rate), 44 (23%) reported providing some form of comprehensive care nurse led clinic, 90% of which were initiated since 1995. Key results show staff development featured as the main reason for initiating such services and there was general consistency in the aspects of care undertaken by these nurses. There was evidence of guideline development specific to nurse led care and some patient group direction use for supplying medication. The level of support from medical staff while nurse led clinics were being conducted varied between services. Few services have conducted any audit or research to monitor/evaluate nurse led care. There was little consistency in the clinical experience and educational prerequisites to undertake comprehensive care nurse led clinics. Continuing professional development opportunities also varied between services. Conclusions: The steady growth of comprehensive care nurse led clinics indicates that the skills of GUM nurses are being recognised. Nurses working in advanced practice roles now require courses and study days reflecting these changes in practice. Locally agreed practice guidelines can define nursing practice boundaries and ensure accountability, as will the development of patient group directions to supply medication. Monitoring and evaluation of nurse led clinics also require attention.